The True Cause of the Punic Wars - Terpstra, Jacob; Waters, Matthew (My University, 2017)
The goal of this research was to study the politics that lead up to the three Punic Wars.
Color poster with text, maps, and images.
Keywords: Greek history; Roman history; Philinus; Punic Wars; Posters